Quality assessment of pharmacoeconomic studies of the use of proton pump inhibitors in peptic ulcer disease (2013)
Proton pump inhibitors (PPI) are a group of drugs that reduce gastric acid secretion and therefore are widely used in the treatment of peptic ulcer. The remarkable prevalence and incidence of this disease suggests that economic and human resources devoted to treatment are considerable and therefore it is necessary to identify reliable sources of information related to the costs and benefits of these therapeutic agents to appraise in terms of efficiency to improve rational prescribing. This paper conducted a review of pharmacoeconomic studies pertaining to the use of ppi in the prevention and treatment of peptic acid disease, as it presents a paired assessment of methodological quality of the literature instrument based on qhes (Ofman et al., [10]). Of the ten articles reviewed, four were cost-effectiveness, two cost-utility, three description of cost, and one of cost minimization. The average overall scored 66.6 out of 100. Four of them scored below 60.0, making it a clear need for pharmacoeconomic evaluations in connection with the use of ppi for prevention and treatment of peptic ulcer, especially cost-effectiveness studies that meet standards of methodological quality.